(a)

f(x)=3x

g(x) =x/3

f(g(x) )=f(x/3)= 3 * x/3 =x

g(f(x)) = g(3x) =3x/3 =x

f and g are inverse of each other

(b)

f(x)=(x+3)/2

g(x)=2x+3

f(g(x))=f(2x+3) =(2x+3+3)/2= (2x+6)/2 =x+3 not equal to x

g(f(x)= g((x+3)/2= 2*(x+3)/2+3 =(x+3+3) =x+6 not equal to x

f and g are not inverse of each other

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up